Circulating LL37 targets plasma extracellular vesicles to immune cells and intensifies Behçet's disease severity. Issue 1 (1st December 2017) - Kahraman, Tamer; Gucluler, Gozde; Simsek, Ismail; Yagci, Fuat Cem; Yildirim, Muzaffer; Ozen, Can; Dinc, Ayhan; Gursel, Mayda; Ikromzoda, Lolai; Sutlu, Tolga; Gay, Stephen; Gursel, Ihsan
ABSTRACT: Behçet's disease (BD) activity is characterised by sustained, over-exuberant immune activation, yet the underlying mechanisms leading to active BD state are poorly defined. Herein, we show that the human cathelicidin derived antimicrobial peptide LL37 associates with and directs plasma extracellular vesicles (EV) to immune cells, thereby leading to enhanced immune activation aggravating BD pathology. Notably, disease activity was correlated with elevated levels of circulating LL37 and EV plasma concentration. Stimulation of healthy PBMC with active BD patient EVs induced heightened IL1β, IFNα, IL6 and IP10 secretion compared to healthy and inactive BD EVs. Remarkably, when mixed with LL37, healthy plasma-EVs triggered a robust immune activation replicating the pathology inducing properties of BD EVs. The findings of this study could be of clinical interest in the management of BD, implicating LL37/EV association as one of the major contributors of BD pathogenesis. Abbreviations : BD: Behçet's disease; EV: extracellular vesicle; BB: binding buffer; AnV: annexin V; autologEV: autologous extracellular vesicles; alloEV: allogeneic extracellular vesicles